Association between body fat distribution and asthma in adults: results from the cross-sectional and bidirectional Mendelian randomization study - Wang, Kang; Chen, Zhujun; Wei, Zhengxiao; He, Lijun; Gong, Liang (Frontiers in Nutrition, 2024)
Background Many studies define obesity based on body mass index (BMI) and explore its relationship with adult asthma. However, BMI only considers height and weight, ignoring other factors such as body fat, which may have a greater impact on health. We investigated the relationship between body fat distribution and adult asthma using both a cross-sectional study and bidirectional Mendelian randomization (MR) analysis. Methods Weighted logistic regression models were used to examine the relationship between body fat distribution measurements and adult asthma in the cross-sectional study from National Health and Nutrition Examination Survey (NHANES) 2011–2018. Restricted cubic spline (RCS) curves were employed to explore the dose–response relationship between them. The inverse-variance weighted (IVW) method was used as the main method of MR analysis to explore the causal effect of exposure on outcome. Results After adjusting for all covariates, weighted logistic regression analysis indicated that fat mass in the left arm, left leg, right arm, right leg, trunk, and total body is associated with an increased risk of developing adult asthma (p < 0.05). RCS curves showed that all six fat mass indicators exhibit a J-shaped relationship with adult asthma. Forward MR analysis found a causal effect of six fat mass indicators on the increased risk of adult asthma (p < 0.05). However, reverse MR did not reveal any causal effect of adult asthma on these six fat mass indicators (p > 0.05). Conclusion Our study supports a positive correlation and a unidirectional causality between body fat distribution measurements and the risk of adult asthma. Further studies are needed to validate our findings.